A geografia da paracoccidiodomicose no estado do Maranhão Brasil - MATOS, Wilma Batista de (2009)
This is a descriptive study type series of cases on Paracoccidioidomycosis (PCM) in the State of Maranhão, carried out in two phases: first, a survey of cases treated cases from 1997 to 2007 at Piauí’s Natan Portela Institute of Tropical Diseases in ( IDTNP), at the Reference Center of Infectious and Parasitic Diseases and at the Pre-Amazon Tropical Medicine Research Center (NEMPTA) of the Federal University of Maranhão, secondly, a study of clinical cases seen by CREDIP from 2004 to 2007 . 216 cases have been cataloged, 197 have been seen at IDTNP, 15 at CREDIP and 4 at NEMTPA. The central and western regions have been the ones presenting the largest number of cases with 22% and 48% respectively. The Pindaré micro-region (58casos), Imperatriz (46casos) and Caxias (24 cases) stood out, showing these are important areas for the studies. The prevalence was higher in men with 88.4% of cases, and the proportion between men and women was 8:1. Most affected people were older than 14 years of age, with residence in the rural area and had farming or soil works as main occupation (67.2%). From the 15 cases diagnosed and treated at CREDIP, only one was considered subacute, and the most common symptom was lymphadenopathy (53.3%). The histopathological tests have been performed in 11 patients with 66.6% of positivity, and direct microscopy has been performed in 12 patients with 73.3% of positivity. Only in one patient the P. brasiliensis could not be found, showing that when there is an accessible lesion the direct microscopic test of material obtained from the lesions should be indicated primarily by its accuracy and simplicity.